Safety exclusive distance of LNG dense gas dispersion and its influencing factors - Sun, Biao; Guo, K. (2010)
Once LNG leaks from the tanks or other containers, the cryogenic heavy gases cloud disperses, accompanying the ensuing gravity driven flow, the density of which is 1.5 times of that of the air. Moreover, since the air is entrained into this cloud by the atmospheric turbulence, the cryogenic heavy gases cloud is thus heated to transform to the positive flotation. In light of this, a study on dense gas dispersion in large-scale LNG leakage was carried out. A calculation method was developed for the safety exclusive distance. Based on the basic DEGADIS (dense gas dispersion) model, a simulation modeling on the dense gas dispersion for large scale LNG release in atmosphere was developed. Compared with other models, this model, which is more adaptable and accurate, was evaluated with the Burro series of LNG spill tests. The average relative deviation was 24.82%. Different requirements for the safety exclusive distance of LNG dense gas dispersion were determined under different conditions.